Malay literacy in painting / Noor Farhani Othman ... [et al.] - Othman, Noor Farhani; Redzuan, Raiha Shahanaz; Anuar, Roslaili; Maaruf, Siti Zuraida; Ahamed Kamal, Akmal; Samsudin, Nor Syamimi (2022)
Art plays a significant role in promoting heritage and sense of belonging. Hence, visual art and Malay literature not only reflect cultural values and aspirations but also as a communication tool for spiritual feedback to society. Research has been done to explore the form and content of Malay literature in paintings. This paper derives from an in-depth study of paintings using Feldman Theory of art criticism. The artists successfully interpreted the philosophical values, aesthetic and creativity of Malay literature in their artworks. It is hope that this research will inspire young artists to take part in using Malay literature and culture as a medium of ideas and further promoting our heritage to the society.